The Illocutionary Speech Acts in Students’ Public Speaking - Pipit Rahayu; Eripuddin Eripuddin (STAI Hubbulwathan Duri, 2023)
Public speaking is not only about sharing information but also about pointing out the speakers’ intentions. There is the meaning should be understood by the hearers. This study discusses the illocutionary speech acts in the students’ public speaking in English Department. This study aims to determine the types of illocutionary speech acts in a formative speech in the sixth semester of the English language education study program at Pasir Pengaraian University. This study was descriptive qualitative. The sample of this research was the sixth-semester students of the English education study program at Pasir Pengarain University. The samples were taken by using the total sample. There were 22 students. The data of this study were obtained using the listening and note-taking technique design about the meaning of utterances containing. The data were analyzed by using Austin's Theory. The result showed three illocutionary speech acts: ten assertiveness, eight directive, four declarative, three commissives, and ten expressive.